2018
DOI: 10.2147/jpr.s164414
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of the analgesic efficacy of pulsed radiofrequency treatment in patients with chronic lumbosacral radicular pain: a retrospective observational study

Abstract: BackgroundPulsed radiofrequency (RF) targeting the adjacent dorsal root ganglion (DRG) is one treatment option for lumbosacral radicular pain. However, the analgesic efficacy of this procedure is not always guaranteed. The aim of this retrospective study was to identify the predictors of the analgesic efficacy of pulsed DRG RF treatment in patients with chronic lumbosacral radicular pain.MethodsPatients who underwent pulsed DRG RF treatment from 2006 to 2017 at our clinic were enrolled. Positive response was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 16 publications
0
15
0
7
Order By: Relevance
“…Although treatment at different targets as well as using different parameters has efficacy in short-term, the longterm relapse rate and numbness grade varied greatly. In a study conducted by Kim et al, histological examinations showed that low-temperature (42°C) radiofrequency therapy for dorsal root ganglion and sciatic nerve caused temporary endothelial edema and collagen deposition of the nerve, while no structural changes were found [10]. According to a study by Erdine et al, electron microscopy demonstrated the damages of axonal ultrastructure, abnormalities of membrane and mitochondria, and collapse of microtubules and microfilaments after undergoing low-temperature radiofrequency therapy [11].…”
Section: Discussionmentioning
confidence: 99%
“…Although treatment at different targets as well as using different parameters has efficacy in short-term, the longterm relapse rate and numbness grade varied greatly. In a study conducted by Kim et al, histological examinations showed that low-temperature (42°C) radiofrequency therapy for dorsal root ganglion and sciatic nerve caused temporary endothelial edema and collagen deposition of the nerve, while no structural changes were found [10]. According to a study by Erdine et al, electron microscopy demonstrated the damages of axonal ultrastructure, abnormalities of membrane and mitochondria, and collapse of microtubules and microfilaments after undergoing low-temperature radiofrequency therapy [11].…”
Section: Discussionmentioning
confidence: 99%
“…En un estudio retrospectivo, Kim y cols. encuentran que la presencia de dolor osteomuscular asociado y una buena respuesta a las inyecciones epidurales de esteroides pueden considerarse factores predictores de respuestas satisfactorias a la radiofrecuencia pulsada del GRD (20).…”
Section: Discussionunclassified
“…Флюороскопический контроль осуществлялся С-аркой (Philips BV Endura), для радиочастотной обработки использовались генератор Radionics RFG 3C Plus, электроды Cosman 100 мм и канюли с рабочей частью 5 мм). Нами применялся трансфораминальный доступ к спинальному ганглию [9,13]. Для проведения доступа использовалась методика туннельной визуализации.…”
Section: материалы и методыunclassified
“…Указанный механизм воздействия назван импульсным радиочастотным воздействием (pulsed radiofrequency -PRF) [7,8]. Для лечения пояснично-крестцовых радикулопатий применяется интервенционное импульсное радиочастотное воздействие на ганглии заднего спинального корешка (DRG) [9]. Впервые оно начало использоваться около 20 лет назад, и за все это время не было отмечено сколько-нибудь серьезных осложнений.…”
Section: Introductionunclassified
See 1 more Smart Citation